Accurate electron channeling contrast analysis of a low angle sub-grain boundary. (December 2015) - Mansour, H.; Crimp, M.A.; Gey, N.; Maloufi, N.
Graphical abstract: Abstract: High resolution selected area channeling pattern (HR-SACP) assisted accurate electron channeling contrast imaging (A-ECCI) was used to unambiguously characterize the structure of a low angle grain boundary in an interstitial-free-steel. The boundary dislocations were characterized using TEM-style contrast analysis. The boundary was determined to be tilt in nature with a misorientation angle of 0.13° consistent with the HR-SACP measurements. The results were verified using high accuracy electron backscatter diffraction (EBSD), confirming the approach as a discriminating tool for assessing low angle boundaries.